Cryptococcus gattii infection in an immunocompetent host in Greece - Andreou, Marina (Med Mycol Case Rep, 2019)
We report a case of a 31-year-old otherwise healthy female with pulmonary cryptococcoma along with cryptococcal meningitis due to Cryptococcus gattii molecular type VGI, in Greece. Combined antifungal treatment and surgical excision of pulmonary cryptococcoma yielded a good response.